Uterine artery embolization for primary postpartum hemorrhage - Tae-Hee Kim (Iranian Journal of Reproductive Medicine, 2013)
Background: Postpartum hemorrhage is the leading cause of severe maternal morbidity and death. A prompt management of uterine artery embolization (UAE) is important for a good outcome. UAE is generally accepted to be a safe and reliable procedure. Objective: To estimate critical patient characteristics influencing the success of UAE for the treatment of emergent primary postpartum hemorrhage. Materials and Methods: This was a cross sectional study that reviewed 121 patients who were diagnosed primary postpartum hemorrhage between February 2002 and December 2009 at a tertiary treatment center among 4,022 deliveries. We evaluated patient clinical characteristics associated with a successful surgical outcome of UAE. Results: The success rate for UAE was 96%. For two cases, UAE complication was associated with fever (>38.5oC). Five patients had problems that required admission to the intensive care unit (ICU). Conclusion: To increase the surgical success rate and lower the number of ICU admissions, the decision to treat primary postpartum hemorrhage using UAE should be based on individual patient clinical findings under the direction of obstetrics staff and an interventional radiologist.